Influencia de la satisfacción laboral en el clima organizacional de los trabajadores del fundo agromorin de la empresa danper trujillo s.a.c. 2013 - Sanchez Gónzales, Luz Raquel (2013)
The research is descriptive, Trujillo performed on the company Danper S.A.C, aiming to know how job satisfaction influences the organizational climate of the Morin agro farm workers. The research includes a systematic and detailed study of the indicators of job satisfaction; as well as organizational climate of the workers, using for that observation, structured interview and questionnaire instruments. The study of organizational climate provides fundamental knowledge to the understanding of labour relations and the quality and efficiency of the organizational action. In these domains, the influence of variables is emphasized in self-realization, labour relations and working conditions indicators included in job satisfaction; with regard to the organizational environment, he pointed out in motivation, communication and commitment to work.